Liver Enlargement Predicts Obstructive Sleep Apnea–Hypopnea Syndrome in Morbidly Obese Women - Scartabelli, Giovanna; Querci, Giorgia; Marconi, Letizia; Ceccarini, Giovanni; Piaggi, Paolo; Fierabracci, Paola; Salvetti, Guido; Cizza, Giovanni; Mazzeo, Salvatore; Vitti, Jacopo; Berger, Slava; Palla, Antonio; et al. (Frontiers in Endocrinology, 2018)
Obstructive sleep apnea-hypopnea syndrome (OSAHS) is frequently present in patients with severe obesity but its prevalence especially in women is not well defined. OSAHS and non alcoholic fatty liver disease (NAFLD) are common conditions, frequently associated in patients with central obesity and metabolic syndrome and are both the result of the accumulation of ectopic fat mass. Identifying predictors of risk of OSAHS may be useful to select the subjects requiring instrumental sleep evaluation. In this cross-sectional study we have investigated the potential role of hepatic left lobe volume in predicting the presence of OSAHS. OSAHS was quantified by the apnea/hypopnea index (AHI) and oxygen desaturation index (ODI) in a cardiorespiratory inpatient sleep study of 97 obese women (age: 47±11 yr, body mass index-BMI: 50±8 kg/m2). OSAHS was diagnosed when AHI was ≥ 5. Hepatic left lobe volume (HLLV), subcutaneous and intra-abdominal fat were measured by ultrasound. After adjustment for age and BMI, both HLLV and neck circumference (NC) were independent predictors of AHI. OSAHS was found in 72% of patients; HLLV ≥370 cm3 was a predictor of OSAHS with a sensitivity of 66%, a specificity of 70%, a positive and negative predictive values of 85% and 44%, respectively (AUC=0.67, p<0.005). A multivariate logistic model was used including age, BMI, NC and HLLV (the only independent predictors of AHI in a Multiple linear regression analyses), and a cut off value for the predicted probability of OSAHS equal to 0.7 provided the best diagnostic results (AUC=0.79, p<0.005) in terms of sensitivity (76%), specificity (89%), negative and positive predictive values (59 and 95%, respectively). All patients with severe OSAHS were identified by this prediction model In conclusion HLLV, an established index of visceral adiposity, represents an anthropometric parameter closely associated with OSAHS in severely obese women.